Impact of War and Resettlement on Vietnamese Families Facing Dementia: A Qualitative Study. Issue 4 (8th August 2022) - Sun, Mengxue; Tran, Duyen; Bach, Anna; Ngo, Uyen; Tran, Tiffany; Do, Thuy; Meyer, Oanh L.
ABSTRACT: Objectives: Most Vietnamese immigrants in the U.S. today arrived as political refugees due to the Vietnam War in the late 20 th century. Refugees are disproportionally affected by health and mental health disparities as a result of experiencing distress and potentially traumatic experiences before, during, and after their migration processes. This study involved Vietnamese families facing dementia and used a qualitative approach to investigate participants' experiences before, during, and right after their resettlement in the U.S. Methods: In-person interviews were conducted with 11 Vietnamese adults who cared for their family member with dementia. A descriptive analysis approach was used. Results: Five major themes emerged from the interviews:1) immigrating separately from family members, 2) difficult and unsafe journeys, 3) experiences of loss, 4) lack of support systems in the U.S., and 5) feelings of unhappiness, sadness, or signs of depression. Conclusions: This study provides a close examination of Vietnamese refugees' unique backgrounds and how individuals with dementia and their caregivers from this population may be disproportionally impacted by stress. Clinical Implications: To reduce health disparities, we recommend that providers and policymakers allocate more resources for culturally appropriate routine assessment, treatment, and referrals of those with dementia and their caregivers.